Electrooptic Modulators with Controlled Frequency Responses by Using Nonperiodically Polarization-Reversed Structure. (11th September 2008) - Pham, Ha Viet; Murata, Hiroshi; Okamura, Yasuyuki
Abstract : We discuss a new method to design traveling-wave electrooptic modulators with controlled frequency responses using nonperiodically polarization-reversed structure. Using our method, the frequency responses of both magnitude and phase of modulation index are controllable. Several electrooptic modulators for advanced modulation formats such as duobinary modulation and wideband single-sideband modulation are proposed.